Diversity of rodents and treeshrews in different habitats in western Sarawak, Borneo. - Teo, S.Z.; Chong, Y.L.; Tuen, , A.A. (The Malaysian Society of Applied Biology, 2021)
A diverse community of 63 rodent species and nine treeshrew species are found in Borneo (Phillipps & Phillipps, 2016). They play an important role in providing ecosystem services by contributing to pollination, seed dispersal, and germination; and also food for larger carnivores (Shanahan & Compton, 2000; Morand et al., 2006; Payne & Francis, 2007; Phillipps & Phillipps, 2016). Bornean tropical forests have been lost, degraded, and fragmented by anthropogenic activities since the early 1970s (Bryan et al., 2013; Gaveau et al., 2014), consequently created new or alternative habitats for rodents and treeshrews especially resilient, adaptive, or opportunistic species that can thrive in such disturbed areas while forest-dependent species would decline in number or become locally extinct (Traweger et al., 2006; Palmeirim et al., 2020). This study was conducted to determine the species richness and abundance of rodents and treeshrews in four different habitats (i.e. forest, oil palm plantation, rural villages, and urban area) in the western part of Sarawak, Borneo. The data collected from this study is important and useful in contributing new knowledge on the occupancy of anthropogenically created habitats for rodents and treeshrews and gives an insight into how each rodent and treeshrew species responded to human disturbance in term of their species richness and abundance in each habitat type.